Gestão pública e saúde ocupacional: contextualização do meio ambiente de trabalho no município de Cachoeiro de Itapemirim - Castro, Bruno Sacre de (2023)
The main objective of occupational safety is to ensure the health of the worker. Although issues related to safety and health of the worker are widely discussed in the private sector, when it comes to the public sector there are several gaps related to the subject. Thus, the research had as a general objective to know the work environment in which the public servants of the Executive Branch of the Municipality of Cachoeiro de Itapemirim are inserted and, as specific objectives, describe the work environment, point out the Municipal Departments that have servants exposed to occupational risks, identify the occupational risks present in the activities and the respective unhealthy framework, verify the positions that work under dangerous conditions and specify the existing control measures. To this end, the Risk Management Programs and the Technical Reports on Environmental Working Conditions of the 18 Municipal Departments were used in the survey carried out in the year 2022. The study included 6,196 municipal civil servants. The description of the work environment was based on the observation of the "environment description" field of the Risk Management Program - RMP of each department. The survey showed that 51% of the servers of the Cachoeiro de Itapemirim City Hall worked in air-conditioned or air-conditioned and ventilated environments, 15% in ventilated environments and only 1% in naturally ventilated environments. As for occupational risks, the study showed that 797 employees were exposed to at least one unhealthy and/or hazardous agent and that 11 departments had at least one employee working in an unhealthy or hazardous situation. It was also observed that 66% of the employees were exposed to more than one environmental agent considered unhealthy and that the highest exposure was for biological agents, followed by chemical and physical agents. Only two Secretariats had servers performing activities considered dangerous. With regard to control measures, it is worth noting the lack of administrative measures and collective protection equipment in the RMPs. Regarding individual protection equipment, it was found that 54% of the exposed workers used it during the work day. The results indicated that there is a big gap in the knowledge about protection measures and control of occupational risks existing in the work environment. The technical-technological product prepared consists of a proposal for a normative instruction (IN) that aims to establish and regulate the procedures that seek to ensure the health and safety of municipal public servants.